PENGEMBANGAN SISTEM PERENCANAAN PEMBELAJARAN - Dion Anugrah; Nursalim Nursalim; Anggi Fitri (Pendidikan Bahasa dan Sastra Indonesia, 2021)
The development of learning concering understanding, improvement, and application of methods in creating learning. The development of learning is an optimum formulation and use of procedures to create new learning in specific situations. The development of learning produces ready-to-use, cursory, and learning plans. The use of learning is the optimum process of deciding and using of optimal procedures ti achieve optimal outcome. The use of learning requires knowledge of the various methods of using, the optimal combination of procedures, and the situations that optimize using models.